Endovascular stenting for idiopathic intracranial hypertension with venous sinus stenosis. Issue 5 (4th April 2019) - Liu, Xinfeng; Di, Hai; Wang, Jun; Cao, Xiangyu; Du, Zhihua; Zhang, Rongju; Yu, Shengyuan; Li, Baomin
Abstract: Objectives: Idiopathic intracranial hypertension (IIH) is characterized by elevated intracranial pressure of unknown etiology and venous sinus stenting may be an optional treatment. We aimed to evaluate the effects of venous sinus stenting on visual function, intracranial pressure, and trans‐stenotic pressure gradient of the patients with IIH and to determine effects of baseline BMI or weight changes on subjective vision outcome and intracranial pressure. Methods: From July 2009 to Aug 2016, 88 eligible patients with IIH and venous sinus stenosis who underwent stenting were retrospectively studied. Results: In this study, 67 women and 21 men were included with an average age of 39.01 (18–60) years. The average BMI was 26.75 kg/m 2 . Here, 66 (75.9%) patients had papilledema, 39 had impaired vision before stenting; 57 patients were followed‐up, 48 (84.2%) showed significant subjective improvement or recovery in visual acuity, 4 (7.0%) patients reported no significant change in visual functions, and 5 (8.8%) suffered permanent vision loss. The cerebrospinal fluid opening pressure and trans‐stenotic pressure gradient were significantly decreased postoperatively. Baseline BMI was associated with pre‐and postoperative trans‐stenotic pressure gradients, as well as changes in cerebrospinal fluid opening pressure. However, baseline BMI and body weight changes during follow‐up were not necessarily associated with subjective visual outcomes after stenting. Stenting efficacy was limited in patients with severe preoperative optic symptoms. Conclusions: Venous sinus stenting represented an effective treatment for resolving visual dysfunction and intracranial pressure associated with venous sinus stenosis. BMI seemed to be associated with intracranial pressure but not subjective visual outcomes after stenting. Abstract : Venous sinus stenting represented an effective treatment for resolving visual dysfunction and intracranial pressure associated with venous sinus stenosis. BMI seemed to be associated with intracranial pressure but not subjective visual outcomes after stenting